2018
DOI: 10.1093/europace/euy285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel cardioversion intervention for atrial fibrillation: the Ottawa AF cardioversion protocol

Abstract: Electrical cardioversion is commonly performed to restore sinus rhythm in patients with atrial fibrillation (AF), but it is unsuccessful in 10-12% of attempts. We sought to evaluate the effectiveness and safety of a novel cardioversion protocol for this arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…The high cardioversion success rates for atrial fibrillation reported using the Ottawa‐atrial fibrillation (AF) cardioversion protocol coupled with our study’s findings send an important message to physicians: that manual pressure augmentation (MPA) and the use of 360 J defibrillators are alternative techniques rather than accepting “permanent AF” after failed cardioversion using 200 J with adhesive patches (as is standard practice at many centers). Of note, some of the patients in our study were referred for inclusion after failed cardioversion elsewhere, and perhaps this more selected population may explain the higher failure rates with 200 J patches observed in our randomized study compared with the observational results reported by Ramirez et al With respect to the methodology of MPA, this was performed in either the AA or AP configuration (50% each) and a single operator performed this on 75% of occasions. Handheld paddles are not routinely available at many Australian hospitals, and hence it was important to report the MPA technique (using gloves) as a safe and effective technique.…”
mentioning
confidence: 74%
“…The high cardioversion success rates for atrial fibrillation reported using the Ottawa‐atrial fibrillation (AF) cardioversion protocol coupled with our study’s findings send an important message to physicians: that manual pressure augmentation (MPA) and the use of 360 J defibrillators are alternative techniques rather than accepting “permanent AF” after failed cardioversion using 200 J with adhesive patches (as is standard practice at many centers). Of note, some of the patients in our study were referred for inclusion after failed cardioversion elsewhere, and perhaps this more selected population may explain the higher failure rates with 200 J patches observed in our randomized study compared with the observational results reported by Ramirez et al With respect to the methodology of MPA, this was performed in either the AA or AP configuration (50% each) and a single operator performed this on 75% of occasions. Handheld paddles are not routinely available at many Australian hospitals, and hence it was important to report the MPA technique (using gloves) as a safe and effective technique.…”
mentioning
confidence: 74%
“…The AADs' success rate is even lower if one assumes that up to 60% of recent-onset AF episodes convert spontaneously in less than 48 h and approximatively 30% of converted patients maintain SR at one year without AADs. Refinement in ECV technique could improve the conversion success rate; one example is the so called Ottawa protocol, consisting of four steps differing in electrode position and energy used [6]. Use of AAD pretreatment is an attractive hybrid modality to increase the ECV success rate (facilitated ECV – FECV).…”
mentioning
confidence: 99%
“…Future prospective randomized studies assessing the superiority of vernakalant for FECV in comparison to other AADs will be needed to validate the therapeutic value of individual AADs for facilitated ECV.
Fig. 1proposed algorithm for facilitated cardioversion.ECV: electrical cardioversion; IRAF: immediate AF recurrence; AAD; antiarrhythmic drugs; Vk: vernakalant; Ad: amiodarone; Fl: flecainide; Pf: propafenone; FECV: facilitated cardioversion.#ECV stepped protocol could be applied before tempting FECV.*During this protocol pressure should be applied on the patient by means of defibrillator paddles [6].
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We congratulate the authors for their interesting study. We recently published the main results of a cardioversion protocol for atrial fibrillation that we tested in a before/after study . Our protocol uses adhesive patches to deliver up to 360 J shocks and incorporates a different approach to MPA.…”
mentioning
confidence: 99%